2017
DOI: 10.5194/tc-11-1091-2017
|View full text |Cite
|
Sign up to set email alerts
|

In situ continuous visible and near-infrared spectroscopy of an alpine snowpack

Abstract: Abstract. Snow spectral albedo in the visible/near-infrared range has been continuously measured during a winter season at Col de Porte alpine site (French Alps; 45.30 • N, 5.77 • E; 1325 m a.s.l.). The evolution of such alpine snowpack is complex due to intensive precipitation, rapid melt events and Saharan dust deposition outbreaks. This study highlights that the resulting intricate variations of spectral albedo can be successfully explained by variations of the following snow surface variables: specific su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(114 citation statements)
references
References 58 publications
(103 reference statements)
2
112
0
Order By: Relevance
“…Higher resolution imagery might help resolve small scale variability around the station that is not resolved in Landsat 30-m data but that is known from the experience of the field visits. The AWS albedo measurements may also be affected by measurement biases due to the natural instability of the substratum on which the AWSs are placed, e.g., tilted surface slope below the downward pyranometer [36] or inaccurate horizontal leveling of the sensor.…”
Section: Discussionmentioning
confidence: 99%
“…Higher resolution imagery might help resolve small scale variability around the station that is not resolved in Landsat 30-m data but that is known from the experience of the field visits. The AWS albedo measurements may also be affected by measurement biases due to the natural instability of the substratum on which the AWSs are placed, e.g., tilted surface slope below the downward pyranometer [36] or inaccurate horizontal leveling of the sensor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the instrumental errors, the surface slope at the footprint scale may influence the retrieval results. Using data from Picard et al (2016), Dumont et al (2017) found variations of the surface slope caused by wind drift at Dome C of ±2 • . They estimated a resulting uncertainty of 10 % in retrieved SSA due to these variations of the surface slope.…”
Section: Retrieval Of Optical Snow Grain Size From Spectral Albedo Mementioning
confidence: 99%
“…Measured quantity Specifications tral Modular Airborne Radiation measurement sysTem (SMART), which applies an active horizontal stabilization of the optical inlets to correct for aircraft movement (Wendisch et al, 2001;Ehrlich et al, 2008). SMART albedo measurements have an estimated uncertainty between 4.1 and 8.1 %, also taking into consideration uncertainties due to the active horizontal stabilization of 1.0 %.…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The AWS albedo measurements may also be affected by measurements biases due to the natural instability of the substratum on which are placed the AWSs, e.g. tilted surface slope below the downward pyranometer [35] or inaccurate horizontal leveling of the sensor.…”
Section: Discussionmentioning
confidence: 99%